Increased Risk of Hypertension with Enzalutamide in Prostate Cancer: A Meta-Analysis. (21st October 2019) - Zhu, Xiaolei; Wu, Shenhong
Abstract: Hypertension is associated with enzalutamide in the treatment of prostate cancer. We performed a meta-analysis of randomized clinical trials to determine the risk of hypertension. Databases including Pubmed and Google scholar were searched to identify randomized clinical trials with enzalutamide. A total of seven studies including 7347 patients were selected. The overall incidences of all-grade and high-grade hypertension were 11.9% (95%% CI: 8.8–16.0%) and 4.9% (95%% CI: 3.5–6.8%) respectively, with a relative risk of 2.82 (95%% CI: 2.34–3.38, p  < 0.001) for all-grade and 2.27 (95%% CI: 1.73–2.96, p  < 0.001) for high-grade. There was a significant risk of developing hypertension with enzalutamide.